Development Of E-Modules In Mangrove Species Diversity Based On Local Potential For Problem Based Learning (PBL) To Enhance Environmental Attitudes - Rachmawati, Rizqi Nur; Rohman, Fatchur; Novianti, Vivi (Universitas Negeri Jakarta, 2024)
This study aims to develop e-modules of mangrove species diversity as local potential in learning. The development model used is the Lee & Owens (2004) development model. There are five phases in the development of research, namely the analysis, design, development, implementation and evaluation. The used learning model is Problem-Based Learning by presenting authentic mangrove problems in Banten. The e-module that has been developed will be tested for validity, practicality and effectiveness so that it can be disseminated for student learning activities. E-modules are tested for validity by conducting a 100% material expert validation test, 98.77% media and teaching material validation results and 100% validation results from field practitioners. Before being used in learning, the e-module was tested for practicality with a one-on-one trial getting a score of 93.33%, a small group trial of 89.41%, a field trial of 86.2% and a field test of 95.04%. Based on the results of student response testing, it can be concluded that the e-module of mangrove diversity is practically used in learning. The results of effectiveness testing to see the improvement of students' environmental attitudes were analyzed. The results of effectiveness testing to see an increase in students' environmental attitudes are measured qualitatively with an N-Gain measurement of 0,46 which is included in medium effectiveness and quantitatively measured using a simple paired t test with p-value of 1.88 which means there is a significant difference before and after using e-module in learning.